Mechanistic Insights into the Anticancer Potential of Methoxyflavones Analogs: A Review - Mohammad Aidiel; Maisarah Abdul Mutalib; Rajesh Ramasamy; Nik Nasihah Nik Ramli; Shirley Gee Hoon Tang; Siti Hajar Adam (Molecules)
2-phenylchromen-4-one, commonly known as flavone, plays multifaceted roles in biological response that can be abundantly present in natural sources. The methoxy group in naturally occurring flavones promotes cytotoxic activity in various cancer cell lines by targeting protein markers, in facilitating ligand–protein binding mechanisms and activating cascading downstream signaling pathways leading to cell death. However, the lipophilic nature of these analogs is a key concern as it impacts drug membrane transfer. While lipophilicity is crucial for drug efficacy, the excessive lipophilic effects in flavonoids can reduce water solubility and hinder drug transport to target sites. Recent in vitro studies suggest that the incorporation of polar hydroxyl groups which can form hydrogen bonds and stabilize free radicals may help overcome the challenges associated with methoxy groups while maintaining their essential lipophilic properties. Naturally coexisting with methoxyflavones, this review explores the synergistic role of hydroxy and methoxy moieties through hydrogen bonding capacity in maximizing cytotoxicity against cancer cell lines. The physicochemical analysis revealed the potential intramolecular interaction and favorable electron delocalization region between both moieties to improve cytotoxicity levels. Together, the analysis provides a useful strategy for the structure–activity relationship (SAR) of flavonoid analogs in distinct protein markers, suggesting optimal functional group positioning to achieve balanced lipophilicity, effective hydrogen bonding, and simultaneously minimized steric hindrance in targeting specific cancer cell types.